Pengaruh Motivasi Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT. PLN (Persero) UP3 Bima - Taufikurrahman Taufikurrahman; Jaenab Jaenab; Muhammad Yusuf (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the effect of work motivation and the physical work environment on the performance of employees at PT. PLN (Persero) UP3 Bima, both partially and simultaneously. The research is associative in nature and applies a quantitative approach. A saturated sampling technique was used, comprising 61 employees. Data were collected through a questionnaire based on a five-point Likert scale and analysed using validity and reliability tests, classical assumption test as well as multiple linear regression processed with SPSS version 26. The findings reveal that work motivation has a positive and significant effect on employee performance, the physical work environment has a positive and significant effect on employee performance, and jointly both variables significantly affect the performance of employees at PT. PLN (Persero) UP3 Bima. The coefficient of determination indicates that most of the variation in employee performance is explained by work motivation and the physical work environment, while the remainder is influenced by other factors outside the model. These results confirm that improving employee performance requires strengthening internal work drive and enhancing the physical conditions of the workplace simultaneously.